Cross cultural competence, human resource management practices, cross cultural adjustment and adaptive performance among Jordanian military leaders in United Nations peacekeeping - Al Shdaifat, Fayez Hamed Abdo (2014)
Numerous studies have been conducted by researchers who are either academicians or practitioners to understand the factors that contribute to the effectiveness of the military leaders in the United Nations‟ peacekeeping missions. However, little is known about the determinants of a military leader‟s adaptive performance in the United Nations missions. Hence a gap remains in the literature. This study fills the gap by examining the relationships that exist between cross-cultural competence, human resource management practices, cross-cultural adjustment and adaptive performance by using a sample of 279 Jordanian military leaders who participated in the United Nations missions. Data was collected using the survey method. The five research questions and the seven research objectives of the study were addressed by performing appropriate descriptive and inferential statistical analyses. The Partial Least Squares Method (PLS) algorithm and the bootstrap techniques were used to test the hypotheses. The findings revealed that there is a significant positive relationship between (a) cross-cultural competence and psychological adjustment, (b) cross- cultural competence and adaptive performance, (c) human resource management practices and psychological adjustment, (d) cross-cultural competences and socio-cultural adjustment, (e) human resource management practices and adaptive performance and (f) psychological and socio-cultural adjustment and adaptive performance. The findings imply that cultural intelligence, emotional intelligence, selection and training are significant in predicting psychological adjustment and adaptive performance among military leaders in the United Nations peacekeeping missions. Moreover, the findings of this study reveal that psychological adjustment mediates the relationship between cross-cultural competence and adaptive performance, implying that cross-cultural competence is related to adaptive performance indirectly, mediated through psychological adjustment. The mediating role played by psychological adjustment helps to explain the underlying process that is responsible for the relationship between cross-cultural competence and adaptive performance of military leaders. The findings of this study have significantly contributed to the advancement of knowledge in the field of cross-cultural management as evidenced by the fact that cross-cultural competence and human resource management factors are vital to facilitate a military leader‟s psychological adjustment and adaptive performance in the United Nations‟ missions